Development of ESD-integrated mathematics teaching materials in the maritime context of the Riau islands - Elvi, Mariyanti; Azmi, Roma Doni; Umara, Yudi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study aims to develop mathematics teaching materials integrated with Education for Sustainable Development (ESD) in the maritime context of the Riau Islands. The study was motivated by the importance of mathematics learning that not only develops conceptual understanding, but also fosters students’ sustainability awareness, particularly in maritime regions facing environmental issues such as energy conservation and marine ecosystem degradation. This research employed a Research and Development (R&D) design based on Plomp’s model, which consists of three phases: preliminary research, prototyping, and assessment. The research subjects were 32 eighth-grade students at SMP Negeri 1 Bintan, selected through purposive sampling. The instruments used included validation sheets and practicality questionnaires. The results showed that the developed teaching materials, consisting of lesson plans and student worksheets, met the criteria for high validity, with validity percentages ranging from 88% to 95%. The practicality test also showed a highly practical category, with percentages ranging from 80% to 90% based on teacher and student responses. The integration of ESD principles and the maritime context made mathematics learning more contextual, meaningful, and relevant to students’ environment. These teaching materials also have the potential to support students’ critical and systematic thinking while fostering awareness and responsible attitudes toward environmental sustainability. Therefore, the ESD-integrated mathematics teaching materials are feasible and practical to be used as an innovative learning alternative to support sustainable education.